RANCANG BANGUN APLIKASI PENENTUAN PERSEDIAAN BERDASARKAN PERAMALAN VOLUME PERMINTAAN PADA UD. ADI JAYA MAKMUR - Akhmad Rizal; Sulistiowati Sulistiowati; Iqnatius Adrian Mastan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Adi Jaya Makmur’s Company is a compnay that sell the material’s building. The address in Gubernur Sunandar Priyo Sudarmo 79 street, on Krian Sidoarjo. It offers some kind of material’s building which are cement, sand, brick, limestone, paints etc. The goods it’s in Adi Jaya Makmur’s Company are all collected from the supplier or manufacturers who has already become colleague in business for the further they can sell to the costumer. In Adi Jaya Makmur’s company itself, they have trading system. Nowadays, we have a lot of rival in business which has effect on trading system volume unstable in Adi Jaya Makmur’s company, especially in some materials, which are Gresik’s cement, brick, sand and coral. The effect of the problems  are the inventory of the some variant of material are overfull rather than sales and the other side the inventory is empty or less so the costumer go to the next store. From the problems above, we make the inventory determination’s application based on the forecasting volume demand-based desktop  with the title “ Design’s Application Inventory Determination Based On The Forecasting Volume Demand On Adi Jaya Makmur’s Company” which capable give a lot of contribution on the company to decide the storage on the next period. The method which is used to do the forecasting is Smoothing model expontial winter’s method. This application that was made giving  the information about the amount of demand for goods and also give for the next period. Based on the implementation’s result and system evaluation, Design’s Application Inventory Determination Based On The Forecasting Volume Demand On Adi Jaya Makmur’s Company demand-based desktop will become the solution for the company to decide the amount of demand for goods to the next period.